2018
DOI: 10.1021/acs.jctc.8b00745
|View full text |Cite
|
Sign up to set email alerts
|

Unphysical Discontinuities in GW Methods

Abstract: We report unphysical irregularities and discontinuities in some key experimentally measurable quantities computed within the GW approximation of many-body perturbation theory applied to molecular systems. In particular, we show that the solution obtained with partially self-consistent GW schemes depends on the algorithm one uses to self-consistently solve the quasiparticle (QP) equation. The main observation of the present study is that each branch of the self-energy is associated with a distinct QP solution a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 106 publications
0
56
0
Order By: Relevance
“…In these cases, the quasiparticle equation can have multiple solutions, making both the GW calculation and interpretation of the result more difficult. The problem also appears for more conventional valence states of small molecules, and recent work has shown that these multiple solutions lead to unphysical discontinuities in quasiparticle energies and that ev GW can exacerbate the problem (Loos et al, 2018; Véril et al, 2018). Just as for experimental spectroscopy, the sensitivity of core states to the local environment makes the GW calculation more challenging than for conventional valence states.…”
Section: Current Challenges and Beyond Gwmentioning
confidence: 99%
“…In these cases, the quasiparticle equation can have multiple solutions, making both the GW calculation and interpretation of the result more difficult. The problem also appears for more conventional valence states of small molecules, and recent work has shown that these multiple solutions lead to unphysical discontinuities in quasiparticle energies and that ev GW can exacerbate the problem (Loos et al, 2018; Véril et al, 2018). Just as for experimental spectroscopy, the sensitivity of core states to the local environment makes the GW calculation more challenging than for conventional valence states.…”
Section: Current Challenges and Beyond Gwmentioning
confidence: 99%
“… 42 Multiple solutions have been reported for a couple of systems. 42 , 47 49 However, typically not more than two possible solutions were found, whereas a multitude of peaks are observed in the spectral function of molecular 1s states at the G 0 W 0 @ PBE level without exception.…”
mentioning
confidence: 99%
“…However, we also observe that, in some cases, unphysical irregularities on the ground-state PES, which are due to the appearance of a satellite resonance with a weight similar to that of the GW quasiparticle peak. [78][79][80][81][82] In order to compute the neutral (optical) excitations of the system and their associated oscillator strengths, the BSE expresses the two-body propagator 4,83 L(1, 2, 1 , 2 ) = L 0 (1, 2, 1 , 2 )…”
mentioning
confidence: 99%
“…This shortcoming has been thoroughly described in several previous studies. [78][79][80][81][82] We believe that this central issue must be resolved if one wants to expand the applicability of the present method.…”
mentioning
confidence: 99%